1996
DOI: 10.1177/002221949602900210
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Substance Use by Mexican American Youth With and Without Learning Disabilities

Abstract: This survey study was designed to (a) investigate the prevalence of minor and major substance use among low socioeconomic status elementary and middle school Mexican American students identified with learning disabilities (LD; n = 150) and without LD (n = 150), and (b) identify psychosocial and environmental risk factors that may lead to the use of various substances among both non-learning disabled (non-LD) students and students with LD in an all-Mexican American sample. No differences were found in the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…For some groups of students with disabilities (SWDs), levels of SM may be higher, as they encounter a greater number of risk factors [2], including medication and health problems, societal enabling, a lack of identification of potential problems, and a lack of accessible and appropriate prevention and treatment services [3]. Furthermore, stresses faced by SWDs may lead to the higher possibility of nicotine addiction, alcohol addiction, or drug addiction [4]. …”
Section: Introductionmentioning
confidence: 99%
“…For some groups of students with disabilities (SWDs), levels of SM may be higher, as they encounter a greater number of risk factors [2], including medication and health problems, societal enabling, a lack of identification of potential problems, and a lack of accessible and appropriate prevention and treatment services [3]. Furthermore, stresses faced by SWDs may lead to the higher possibility of nicotine addiction, alcohol addiction, or drug addiction [4]. …”
Section: Introductionmentioning
confidence: 99%
“…While some of these assertions have been evidence-based, many of these arguments are based on moral or political agendas. However, other studies have found inverse associations between U.S. acculturation and drug use (Katims et al, 1996;McCuller et al, 2001) or no significant association after controlling for confounding variables (Brook et al, 1997;Kaplan et al, 2002;Tschann et al, 2002). Other researchers have cited processes that co-occur with integration into the U.S. culture, including the loss of posited protective cultural values and support systems from the culture of origin, the identity confusion associated with attempting to navigate two cultures simultaneously, the marginalization and discrimination associated with being an ethnic minority, or the family conflict that can result when adolescents and their parents acculturate at different rates (Alaniz, 2002;Felix-Ortiz and Newcomb, 1995;Portes and Rumbaut, 2001).…”
Section: How Might Acculturation and Cultural/ Ethnic Identity Affectmentioning
confidence: 96%
“…With respect to alcohol use, the literature is fairly consistent. Most studies conclude that students with and without mild academic disabilities are comparable with respect to their alcohol use (Fakier & Wild, ; Katims & Zapata, ; Kepper et al., ; Maag & Irvin, ), although one study found that students with a disability reported lower levels of alcohol use compared to those without disabilities (McCrystal et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Maag and Irvin () found that conduct disorder, hyperactivity, and emotional problems were not reliable predictors of substance use in both students with or without mild academic disabilities. Additionally, Katims and Zapata () found that deviant behavior (e.g., damaging property, staying out late without permission, carrying a weapon) was associated with substance use in both students with and without mild academic difficulties. Both studies (Katims & Zapata, ; Maag & Irvin, ) investigated the predictive value of behavioral and emotional problems on substance use within both groups of students, providing information on whether these two groups showed the same or different risk factors of substance use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation